1977
DOI: 10.1073/pnas.74.10.4439
|View full text |Cite
|
Sign up to set email alerts
|

Use of 125 I-labeled phytochrome to quantitate phytochrome binding to membranes of Avena sativa

Abstract: Purified oat phytochrome was labeled with 125 I without altering the photoreversibility or absorbance properties of the pigment. The radiolabeled phytochrome was used in experiments in vitro to quantitate the binding of the pigment to both crude and purified membrane preparations from oat tissue. After the membranes were allowed to react with 125 I-labeled phytochrome, washed free of unbound material, and pelleted, they were found to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1978
1978
1983
1983

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…These results do strongly support the postulate that the reactant phytochrome molecules are physically interacting with the mitochondrial membranes; and they encourage a further investigation into the possibility that there are specific binding sites for phytochrome on the mitochondria membrane, as suggested by earlier data (12). Related to this question may be the fact that NADH-dehydrogenase is a flavin mononucleotide-containing flavoprotein, and recent data from W. Smith's laboratory suggest that phytochrome may interact very specifically with flavin mononucleotide in vitro (28).…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…These results do strongly support the postulate that the reactant phytochrome molecules are physically interacting with the mitochondrial membranes; and they encourage a further investigation into the possibility that there are specific binding sites for phytochrome on the mitochondria membrane, as suggested by earlier data (12). Related to this question may be the fact that NADH-dehydrogenase is a flavin mononucleotide-containing flavoprotein, and recent data from W. Smith's laboratory suggest that phytochrome may interact very specifically with flavin mononucleotide in vitro (28).…”
Section: Discussionsupporting
confidence: 71%
“…Our finding that highly purified phytochrome could bind to mitochondria with a reproducible stoichiometry suggested that there were a limited number of phytochrome binding sites on mitochondria; and competition experiments suggested that these sites were relatively specific for phytochrome (12). Although the intact outer membrane of mitochondria is not freely permeable to molecules larger than 12,000 mol wt (8), phytochrome is probably large enough to span this membrane (29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The potency of the present batch of colchicine was verified by testing its effect on cell division in a culture of Chiamydomonas reinhardtii. Cell division was completely blocked by 10 m 3 of the drug (data not shown). CONCLUSIONS The present data show that the intracellular dark reaction responsible for enhanced phytochrome pelletability proceeds with a t1/2 of 2 sec at 25 C following Pfr formation in both maize and Avena.…”
mentioning
confidence: 97%